UTX is an escape from X-inactivation tumor-suppressor in B cell lymphoma - Xiaoxi Li (Nature Portfolio, 2018)
UTX is a tumor suppressor gene located on the X-chromosome so it could potentially contribute to the cancer gender bias. Here the authors, using a mouse model of B cell lymphoma, show that UTX is a dosage sensitive tumor suppressor and may be responsible for some of the increased incidence and possibly aggressiveness of male cancers that harbour UTX mutations.